Linc01194 acts as an oncogene in colorectal carcinoma and is associated with poor survival outcome - Wang X; Liu Z; Tong H; Peng H; Xian Z; Li L; Hu B; Xie S (Cancer Management and Research, 2019)
Xiaoxue Wang, Zhimin Liu, Hong Tong, Hui Peng, Zhenyu Xian, Li Li, Bang Hu, Shangkui Xie Department of Proctology, The Sixth Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China Background: The incidence of colorectal cancer ranks among the top three malignant tumors, attributing to more than 50,000 deaths in the United States every year. Survival rate is directly correlated with TNM stage at diagnosis, and identifying the molecules involved in the cancer development process will provide directions to better investigate the mechanisms of colorectal cancer.Materials and methods: Bioinformatics analysis of differentially expressed long noncoding RNAs (lncRNAs), survival analysis, cell proliferation assay, migration assay, and Western blot analysis were performed.Results: Fifty-one lncRNAs were identified between the early stage and late-stage groups. In the survival analysis, we found that Linc01194 is correlated with poor survival of colon cancer patients. In addition, by suppressing the expression of Linc01194 in colon cancer cell lines, cell proliferation and migration were inhibited. Western blot showed that N-cadherin and vimentin were downregulated, whereas E-cadherin was upregulated indicating that the process of epithelial–mesenchymal transition (EMT) was restrained.Conclusion: Linc01194 promotes the proliferation and migration ability of colon cancer cells by activating EMT. It acts as an oncogene in colorectal carcinoma and is associated with worse survival outcome. Keywords: colorectal cancer, TCGA, lncRNA, Linc01194, EMT